Being patient with microfinance: The impact of training on Indian self help groups - Ranjula Bali Swain; Adel Varghese (Uppsala University, Department of Economics, 2010)
We evaluate the impact of training provided by facilitators of Self Help Groups (SHGs). This evaluation provides one of the first studies of the impact of 'microfinance plus', or the disbursement of services beyond credit. Indian SHGs are mainly NGO-formed microfinance groups but funded by commercial banks. We correct for membership selection bias with data on current as well as future SHG members. We then account for potential training endogeneity with propensity score matching. Regression and unadjusted matching results indicate that training does not aid in asset accumulation but can reverse the negative impact of credit on income. However, regression adjusted matching which controls for both participation and training selection bias reveals that training impacts assets but not income. These results are robust to sensitivity analyses performed on these estimates.
urn:nbn:se:uu:diva-138914
Keywords: G21; I32; O12; 330; India; microfinance; training; impact studies; Self Help Groups; Mikrofinanzierung; Selbsthilfeförderung (Entwicklungsländer); Wirkungsanalyse; Indien